A qualitative assessment on the impact of the youth development programme of the Chrysalis Academy in Cape Town on the lives of past participants - Davids, Thandiwe (Department of Social Development, 2019)
Youth unemployment and crime is a serious problem in South Africa. Young people form the majority of the South African population (Barrar, 2010) and as future leaders and decision makers, it is vitally important to focus on youth and their future prospects. It is for this reason that this study examines youth development in the context of South Africa’s young democracy. This research explored the experiences of young people who had completed a skills training programme at the Chrysalis Academy in Cape Town. Chrysalis Academy is an initiative of the Western Cape Provincial Government. The programme was developed to address crime in poor communities as a preventative measure rather than a rehabilitative one; it aimed to provide skills training to youth to enable them to obtain employment in the hope of preventing their engagement with a life of crime, gangsterism, and drug and alcohol abuse.This study was based on a qualitative, exploratory, descriptive research design and therefore in depth, qualitative interviews were conducted with 15 past students who had graduated from the academy within the past five years. The findings of the research showed that the Chrysalis programme was unique in many respects. Its approach and subject matter as well as the learning techniques offered were different to those many of the participants had previously encountered. The programme offered the students valuable knowledge and skills, which they were able to utilize in their lives after the completion of the programme. There were, however, limitations identified in the programme and recommendations in response to these limitations are made at the conclusion of this paper.